Pengaruh Tempat Tumbuh Tanaman Daun Gaharu (Aquilaria malaccensis Lam) dari Dua Daerah yang Berbeda terhadap Aktivitas Antioksidan - Aris Suhardiman; Wempi Budiana (Jurnal Kartika Kimia, 2023)
Where it grows can affect the content of its compounds, this will also affect the activity test being studied. This study used gaharu leaves from two different regions, namely from Palembang and Bogor. The aim of the study was to determine the antioxidant activity of Palembang and Bogor gaharu leaves and to determine the total flavonoid content. The research method began with sample preparation, simplicia characterization then extracted by maceration using 96% ethanol, then fractionated by liquid – liquid extraction using n-hexane, ethyl acetate, methanol:water solvents. Extracts and fractions were monitored using TLC and tested for antioxidant activity using the DPPH (1,1-Diphenyl-2-Pikrihidrazil) method using a UV-Vis spectrophotometer where the intensity of antioxidant activity was determined by the IC50 value and the determination of total flavonoid content. IC50 results of Palembang gaharu leaves ethanol extract, methanol:water fraction, ethyl acetate fraction, n-hexane fraction respectively 47.44, 71.98, 84.30 and 138.81 µg/ml while Bogor gaharu leaves extract ethanol, methanol fraction : water, ethyl acetate fraction, n-hexane fraction respectively 45.57, 66.39, 81.12, and 140.09 µg/ml. The total flavonoid content of Palembang gaharu leaves was 13.452 QE/g and that of Bogor gaharu leaves was 11.254 QE/g. In conclusion, the ethanol extract of Palembang gaharu leaves is stronger in antioxidants than Bogor gaharu leaves. Directly proportional to the total flavonoid content, this is thought to be due to the influence of the place where it grows, such as soil nutrient content, temperature, climate, and sunlight intensity.